On the stacking fault forming probability and stacking fault energy in carbon-doped 17 at% Mn steels via transmission electron microscopy and atom probe tomography. (10th July 2022) - Bae, Hyo Ju; Ko, Kwang Kyu; Ishtiaq, Muhammad; Kim, Jung Gi; Sung, Hyokyung; Seol, Jae Bok
Highights: We experimentally determined the P sf and SFEs of austenite/ε-martensite dual-phase Fe–17Mn– x C ( x  = 0–0.2 wt.%) steels through electron diffraction analysis. The role of carbon-doping contents on the structural properties, such as the segregation free energy of carbon at grain boundaries, austenite lattice parameter, and mean width of intrinsic stacking faults, was uncovered via atom probe tomography and transmission electron microscopy. We find that increasing amounts of carbon doping give rise to the increased SFE from 8.6 to 13.5 mJ/m 2 with non-linear variation The SFE trend varies, described here, inversely with the mean width of localized stacking faults, which pass through both other stacking faults and preexisting ε-martensite plates without much difficulty at their intersecting zones. Localized intrinsic stacking-faults and their intersecting zones with thermally induced ε-martensite are insufficient for strengthening undoped and carbon-doped 17 wt.% Mn steels with low SFEs. The large amount of carbon doping in the steel yields two effects: increasing the segregation free energy (due to more carbon at grain boundaries) and larger lattice expansion (due to increased soluble carbon at internal grains). Abstract: Assessing the stacking fault forming probability ( P sf ) and stacking fault energy (SFE) in medium- or high-Mn base structural materials can anticipate and elucidate the microstructural evolution before and after deformation. Typically, these two parameters have been determined from theoretical calculations and empirical results. However, the estimation of SFE values in Fe–Mn–C ternary systems is a longstanding debate due to the complicated nature of carbon: that is, whether the carbon doping indeed plays an important role in the formation of stacking faults; and how the amount of carbon atoms exist at grain boundaries or at internal grains with respect to the nominal carbon doping contents. Herein, the use of atom probe tomography and transmission electron microscopy (TEM) unveils the influence of carbon-doping contents on the structural properties of dual-phase Fe–17Mn– x C ( x  = 0–1.56 at%) steels, such as carbon segregation free energy at grain boundaries, carbon concentration in grain interior, interplanar d -spacings, and mean width of intrinsic stacking faults, which are essential for SFE estimation. We next determined the P sf values by two different methods, viz., reciprocal-space electron diffraction measurements and stacking fault width measurements in real-space TEM images. Then, SFEs in the Fe–17Mn– x C systems were calculated on the basis of the generally-known SFE equations. We found that the high amount of carbon doping gives rise to the increased SFE from 8.6 to 13.5 mJ/m 2 with non-linear variation. This SFE trend varies inversely with the mean width of localized stacking faults, which pass through both other stacking faults and pre-existing ε-martensite plates without much difficulty at their intersecting zones. The high amount of carbon doping acts twofold, through increasing the segregation free energy (due to more carbon at grain boundaries) and large lattice expansion (due to increased soluble carbon at internal grains). The experimental data obtained here strengthens the composition-dependent SFE maps for predicting the deformation structure and mechanical response of other carbon-doped high-Mn alloy compositions.